Integrating the Indigenous Knowledge of Borana Pastoralists into Rangeland Management Strategies in Southern Ethiopia - World Bank (World Bank, Washington, DC, 2012)
Pastoralists' indigenous knowledge (IK) about ecology and social organization led to rangeland-management strategies appropriate to deal with the erratic rainfall in African drylands. Herd mobility was traditionally practiced as the key strategy to make use of the scattered rangeland resources on a large scale.